Estimate missing value by use analyses of covariance method for split block-design - خلف المشهداني كمال علوان; كامل سيماء فراس (Journal of Economics and Administrative Sciences, 2017)
The research aims to estimate missing values using covariance analysis method Coons way to the variable response or dependent variable that represents the main character studied in a type of multi-factor designs experiments called split block-design (SBED) so as to increase the accuracy of the analysis results and the accuracy of statistical tests based on this type of designs. as it was noted in the theoretical aspect to the design of dissident sectors and statistical analysis have to analyze the variation in the experience of experiment )SBED) and the use of covariance way coons analysis according to two methods to estimate the missing value, either in the practical side of it has been implemented field experiment wheat crop in rice research station in the city of Mashkhab affiliated to the Department of Agricultural Research / ministry of agriculture it was the experiment with three replications by 36 treatment Area ( 15 square meters each treatment) it has been cultivating first date (15/11/2015) and the second deadline (1/12/2015) and the third deadline (1/12/2015) class grist (aebaa 99) The four seed rates (30/40/50/60) Kg per acre according to Split-block design And as such represents a study winning weight (grains of wheat) as a variable response (Y) data were analyzed using the program (MATLAP) and using equations and formulas in the theoretical side. And ensure the application of the practical side estimate missing values using analysis of covariance in accordance with the design of dissident sectors in two ways and analyze the variation of the recipe studied ((y weight of the crop wheat cereal tons / ha after estimating the lost value.